Evaluation of Pavement Structural Number and Resilient Modulus in a Schistose Quartzite/Quartzite Environment using Dynamic Cone Penetration Test Data: Consequence for flexible pavement construction - Olumuyiwa Falowo; A.S. Daramola; W.K. Olabisi (Kashmir Journal of Science)
The serviceability performance and design life expectancy of pavements depends to a large extent on the strength coefficients, and structural number of the pavement structure as a whole. Hence, this study determines (through in situ dynamic cone penetration test) important geotechnical attributes of the foundation soil in the campus of Rufus Giwa Polytechnic, Owo, southwestern Nigeria, correlates the stiffness properties (in terms of subgrade and elastic modulus). The DCPT penetrative indexes at refusal ranged from 0.1 to 6.4 mm/blow, with average cumulative number of blows of 97. The average CBR value of the subgrade and subbase/base are 33 % and 66 % respectively.  The average strength coefficients for subbase (0.08) and base (0.097) showed that the soil has higher strength for base layer than subbase course. . The estimated Structural Number is 3.59, which is capable of sustaining any imposed traffic load. The average subgrade moduli and elastic moduli of the soil are 439 MPa and 1167 MPa accordingly, with schistose derived soil showing better subgrade strength properties in terms of MR/ES, of 458/1258MPa than quartzite (387/924MPa). Regression model showed weak positive correlation coefficients for MR and ES of quartzite and schistose quartzite for different trend lines.